Czy program 500+ podwyższył osiągnięcia szkolne uczniów z biedniejszych rodzin? - Krzysztof Konarzewski (Problemy Wczesnej Edukacji)
Two models of the poverty effect on school achievement were defined: insufficient expenditure and refusal of recognition. The first of them was verified, using the selective increase in the income of the poorer part of the Polish parents’ population in 2016–2019 by the state support for families with children, Family 500+. Data on achievement in mathematics and science and attitudes towards school and learning of Polish fourth-graders from two editions of the TIMSS survey: 2019 and 2015 were compared. In the 2019 cohort, there was no increase in the achievement of lower-class students, despite the fact that their families received the largest funds from the 500+ program. The model of insufficient expenditure has not been validated but has not been overturned either due to validity limitations of the study.